Production and Partial Purification of Heat-Stable Enterotoxin (A) Produced by Enterotoxigenic Escherichia coli: Rajiha I. Al-Nuaimy, Zaid K. Kamona, Maha F. Al-Taee - Al-Nuaimy, Rajiha I.; K. Kamona, Zaid; F. Al-Taee, Maha (The Iraqi Journal of Veterinary Medicine, 2010)
A total of (25) stool samples were collected from children and adults (2- 4) years oldsuffering from diarrhea to isolate E. coli strains that produce heat-stable enterotoxin a (STa),and after performing microscopic examination, cultural characterization and biochemicalidentification only (11) isolates showed positive E. coli. STa activity was estimated by usingsuckling mouse assay (SMA) and from these (11) isolates only (5) showed STa activity andthe one with the highest STa activity was selected for large scale production of STa, whichwas followed by partial purification using ion-exchange chromatography (normal phase)using DEAE sephadex A-50 column. After purification and determination of proteinconcentration by using the standard curve of bovine serum albumin, the concentration oftoxin-protein was estimated as (1.08) mg/ml. The specific activity varied from (350) U/mgprotein at the first step of purification to (2366.6) U/mg protein at the final step, while thefinal purification of the toxin was about (6.76) fold and with a yield of (18.25) %.